The impact of socioeconomic position on severe maternal morbidity outcomes among women in Australia: a national case–control study. (17th September 2014) - Lindquist, A; Noor, N; Sullivan, E; Knight, M
<x xml:space="preserve">Abstract</x> Objective Studies in other developed countries have suggested that socioeconomic position may be a risk factor for poorer pregnancy outcomes. This analysis aimed to explore the independent impact of socioeconomic position on selected severe maternal morbidities among women in Australia. Design A case–control study using data on severe maternal morbidities associated with direct maternal death collected through the Australasian Maternity Outcomes Surveillance System. Setting Australia. Population 623 cases, 820 controls. Methods Logistic regression analysis to investigate differences in outcomes among different socioeconomic groups, classified by Socio‐Economic Indexes for Areas (SEIFA) quintile. Main outcome measures Severe maternal morbidity (amniotic fluid embolism, placenta accreta, peripartum hysterectomy, eclampsia or pulmonary embolism). Results SEIFA quintile was statistically significantly associated with maternal morbidity, with cases being twice as likely as controls to reside in the most disadvantaged areas (adjusted OR 2.00, 95%CI 1.29–3.10). Maternal age [adjusted odds ratio (aOR) 2.20 for women aged 35 or over compared with women aged 25–29, 95%CI 1.64–3.15] and previous pregnancy complications (aOR 1.30, 95%CI 1.21–1.87) were significantly associated with morbidity. A parity of 1 or 2 was protective (aOR 0.58, 95%CI 0.43–0.79), whereas previous caesarean delivery was associated with maternal morbidity (aOR 2.20 for women with one caesarean delivery, 95%CI 1.44–2.85, compared with women with no caesareans). Conclusion The risk of severe maternal morbidity among women in Australia is significantly increased by social disadvantage. This study suggests that future efforts in improving maternity care provision and maternal outcomes in Australia should include socioeconomic position as an independent risk factor for adverse outcome.